Focus on one swimming stroke or compete in multiple: How much specialization is needed to become a world-class female swimmer? - Born, D. P.; Lorentzen, J.; Ruiz-Navarro, J. J.; Stöggl, T.; Romann, M.; Björklund, G. (Journal of Functional Morphology and Kinesiology, 2016)
Objectives: To investigate performance development and variety in swimming strokes of female swimmers from early junior to elite age. Methods: A total of 194,788 race times of female 200 m swimmers representing 77 nations were ranked at peak performance age and clustered into world-class finalists (>850 swimming points), international-class (750-850), national-class (650-750) and regional-class swimmers (550-650). Annual best times for each swimming stroke were retrospectively extracted throughout adolescence from 13 years of age. Longitudinal performance development and differences between the swimmers` main and their secondary swimming strokes were analyzed using linear mixed model. Results: World-class freestyle swimmers show significantly (p = 0.042) higher swimming points across all age categories compared to international-, national- and regional-class swimmers. Linear mixed model analysis indicates a significant performance progression for international- and national-class freestyle swimmers up to the 19-20-year-old category (p = 0.038), but an earlier plateau was observed for regional-class swimmers (p = 0.714). Comparing main and secondary swimming strokes, freestyle swimmers show the highest degree of specialization. For breaststroke and individual medleys, specialization increases with increasing performance level and the closer an athlete is to elite age. World-class butterfly and backstroke finalists show the lowest specializations in terms of the smallest number of significant differences compared to performances in their secondary swimming strokes. Conclusions: Higher ranked swimmers show a greater degree of specialization. As different specialization patterns are evident for the various swimming strokes, decision makers and talent specialists should align development guidelines accordingly and base them on the most advantageous combinations of swimming strokes.